Supplier selection risk: A new computer-based decision-making system with fuzzy extended AHP - Marcus Vinicius Carvalho Fagundes; Bernd Hellingrath; Francisco Gaudêncio Mendonça Freires (Logistics, 2021)
Supplier risks have attracted significant attention in the supply chain risk management literature. In this article, we propose a new computational system based on the "Fuzzy Extended Analytic Hierarchy Process (FEAHP)" method for supplier selection while considering the relevant risks. We sought to evaluate the opportunities and limitations of using the FEAHP method in supplier selection and analyzed the support of the system developed through the real case of a Brazilian oil and natural gas company. The computational approach based on FEAHP automates supplier selection by determining a hierarchy of criteria, sub-criteria, and alternatives. First, the criteria and sub-criteria specific to the selection problem were identified by the experts taking the relevant literature as a starting point. Next, the experts performed a pair-wise comparison of the predefined requirements using a linguistic scale. This evaluation was then quantified by calculating the priority weights of criteria, sub-criteria, and alternatives. The best decision alternative is the one with the highest final score. Sensitivity analysis was performed to verify the results of the proposed model. The FEAHP computer approach automated the supplier selection process in a rational, flexible, and agile way, as perceived by the focal company. From this, we hypothesized that using this system can provide helpful insights in choosing the best suppliers in an environment of risk and uncertainty, thereby maximizing supply chain performance.
Keywords: 650; AHP; decision-making system; Fuzzy logic; multi-criteria programming; supplier selection risk